Prevalence of malignancies in inflammatory bowel disease patients on immunosuppressants - Sobazile, Loyiso (My University, 2020)
Crohn’s disease (CD) and ulcerative colitis (UC) are chronic idiopathic inflammatory bowel diseases (IBD) with distinct and overlapping clinical and pathological features. Most CD patients and some UC patients will require immunosuppressive (IS) therapy to control bowel inflammation and the resulting complications. Unfortunately IS therapy has been shown, in IBD and in other settings such as solid organ transplant, to increase the risk of extra-intestinal malignancies. To understand the association between cancer and IS therapy in IBD patients, I have conducted a retrospective single-center study in an urban area in South Africa. STUDY DESIGN AND METHODS: This retrospective record review study was done at Charlotte Maxeke Johannesburg Academic Hospital Gastroenterology Clinic (CMJAH) affiliated with Wits University. A total of 202 clinic files from our IBD cohort database were retrieved and analyzed. The diagnosis of IBD was made between 1980 and January 2017. Commonly used drugs were azathioprine (AZA) and methotrexate (MTX). Information about the histopathological diagnosis of IBD and malignancy was confirmed using data from National Health Laboratory Services (NHLS) and Disa*Lab. RESULTS: Among the 99 patients who received IS therapy, 8 (8.08%) patients developed cancer. Age at IBD diagnosis (adjusted hazard ratio [HR] 1.05, 95% CI 1.00 – 1.10) and exposure to IS therapy (HR 11.01, 95% CI 1.27 – 95.28) had significant associations with cancer development (both p<0.05). Six of the patients who developed cancer were on thiopurines. Non-melanoma skin cancer (NMSC) and renal cell carcinoma (RCC) were more prevalent. CONCLUSION: Patients on IS therapy are 11 times more likely to develop malignancies than those who are not. Patients with IBD on IS should be counselled about the risk of cancer. Regular age-appropriate cancer screening is recommended.
A research report submitted to the Faculty of Health Sciences, Wits University, Johannesburg, in partial fulfillment of the requirements for the degree of Masters of Medicine (MMED) in the department of Internal Medicine